Risk Assessment of BRONJ in Oncologic Patients Treated with Bisphosphonates: Follow-Up to 18 Months. (1st September 2014) - Sparabombe, Scilla; Vitali, Lucia; Nori, Alessandra; Berlin, Ricarda Sara; Mazur, Marta; Orsini, Giovanna; Putignano, Angelo
Abstract : Objectives. Bisphosphonates related osteonecrosis of the jaw (BRONJ) is a pathological condition characterized by bone exposure or latent infection in patients treated with the drug. The aim of the study is to monitor the BRONJ level of risk health in patients with cancer, according to a preventive clinical protocol, which is firstly aimed at reducing risk factors such as the periodontal infections. Materials and Methods. 10 patients participated in the protocol and were evaluated at baseline and after 3 and 18 months of treatment with bisphosphonates, through full mouth plaque and bleeding scores (FMPS and FMBS), clinical attachment level (CAL) measurement, and the occurrence of osteonecrosis. Results. The mean plaque and bleeding were reduced and the CAL has not shown significant changes and in no cases was there manifestation of BRONJ. Conclusion. The protocol proved crucial for the maintenance of good oral health conditions by eliminating the risk of BRONJ during the observation period.